Odpowiedzi

Najlepsza Odpowiedź!
2009-11-07T20:36:59+01:00
A)[ 2(do 19)*3(do6)+15*2(do18)*3(do8)]:[2(do11)*3(do9)+(3*4)(do10)]=
( 2(do18)*3(do6))*[2+15*9]:[2(do11)*3(do9)+3(do10)*2(do20)]=
( 2(do18)*3(do6))*[2+135]:[(2(do11)*3(do9))*(1+3*2(do9))]=
137*( 2(do18)*3(do6)):[(2(do11)*3(do9))*(1+3*512)]=
137* (2(do18)*3(do6)):[(2(do11)*3(do9))*(1537)]=
137/1537*( 2(do9)*3(do-3))

b)(25)(do 3/2) *5 (do1/3):[5(do4/5)*5(2/3)]=
5 (do 3)*5(do 1/3):[5(do 4/5+2/3)]=
5 (do 10/3):[5(do 12/15+10/15)]=
5(10/3):[5(do 22/15)]=
5(do 50/15):[5(do 22/15)]= 5 (do 28/15)